2023
DOI: 10.1159/000529426
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition Predictors of Complicated Crohn’s Disease

Abstract: Background: High visceral adipose tissue (VAT) and creeping fat (CrF) in Crohn's disease (CD) have been widely recognized. The VAT to subcutaneous adipose tissue (SAT) ratio and sarcopenia have been associated with CD complications. Studies regarding the influence of body composition predictors on CD complications assessed with magnetic resonance enterography (MRE) are scarce. Aim: Assessment of the body composition parameters and CrF in opportunistic MRE as predictors of complicated CD. Methods: This was a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(93 reference statements)
1
3
0
Order By: Relevance
“…*p < 0.05, ns p > 0.05 (not significant). although our study revealed variability in some body composition parameters among CD patients with different disease behaviors, it was not their independent correlate, which is consistent with the results of a recent study (50). This may be because intestinal complications such as stricture or penetration are a further progression of poorly controlled disease activity and are influenced by a combination of factors such as altered body composition, poor drug therapy and an active intestinal inflammatory response; therefore, altered body composition is not an independent correlate of complex disease behavior.…”
Section: Discussionsupporting
confidence: 92%
“…*p < 0.05, ns p > 0.05 (not significant). although our study revealed variability in some body composition parameters among CD patients with different disease behaviors, it was not their independent correlate, which is consistent with the results of a recent study (50). This may be because intestinal complications such as stricture or penetration are a further progression of poorly controlled disease activity and are influenced by a combination of factors such as altered body composition, poor drug therapy and an active intestinal inflammatory response; therefore, altered body composition is not an independent correlate of complex disease behavior.…”
Section: Discussionsupporting
confidence: 92%
“…Our MRE technique has been previously described, the MRI sequences are depicted in the Table S1 27,28 . All CT examinations were performed on a multidetector CT scanner (Siemens Somatom Definition AS+, Siemens Healthineers, Germany; Canon Aquilion Prime, Canon Medical Systems Corporation, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Our MRE technique has been previously described, the MRI sequences are depicted in the Table S1. 27,28 All CT examinations were performed on a multidetector CT scanner (Siemens Somatom Definition AS+, Siemens Healthineers, Germany; Canon Aquilion Prime, Canon Medical Systems Corporation, Japan). The CT protocol was as follows: acquisition slice thickness of ≤2 mm; tube voltage, 120 kV; automatic tube current modulation; pitch factor, 1.2.…”
Section: Ct and Mre Techniquementioning
confidence: 99%
“…Each MRE was performed on a 1.5 Tesla MR scanner (Intera, Philips Healthcare, Best, Netherlands) in a supine position using a whole-body surface coil system. Our MRE protocol has been previously reported, and the MRI sequences are summarized in Supplementary Table SI [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%